MOTIVASI KELOMPOK TANI HUTAN WONOREJO DALAM PENGELOLAAN HUTAN KEMASYARAKATAN DI DESA KATONGAN, KECAMATAN NGLIPAR, KABUPATEN GUNUNGKIDUL, YOGYAKARTA - , RIZA RAMADHANA S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Community forestry (HKm) is a state forest cover neither the forest protected areas nor co-managed production forest communities with contracts given time. Allegedly motivation owned by Social Forestry Farmers Group (KTHKm) members will affect the management of community forestry. This study aims to determine the motivation KTHKm in the management of community forest, factors that influence motivation and motivation influence the actions KTHKm. The study was carried out in HKm Wonorejo, Katongan, Nglipar, Gunungkidul, Yogyakarta by using a quantitative approach with a survey method. Data was collected by interview, observation and documentation. Analysis of the data using a data analysis method of Miles and Huberman (1992). The KTHKmâs motivation of managing forests are physiological needs, safety needs, social needs, esteem needs and self-actualization needs. There are internal factors and external factors affecting KTHKm in managing forests. The Internal factors are education, experience as a farmer and the narrowness of private land. The external factor are pushing by parent, presence of the staple crops, saving for posterity and preservation of springs. The KTHKmâs influnce to the forest mangement action motivates physiological needs of forest land that use change and basic plant care, safety needs motivation that affects forest protection activities, social needs that affect motivation intensity group gathering and selfactualization needs motivation that affect the use of new strategies in the use of forest